Specialised Nurses for Organ and Tissue Donation; Creation of a New Profile in our Hospital. (August 2017) - Brousoz, S.; Moretti, D.; Arnaud, E.; Flatres, S.; Freitas, C.; Hechinger, S.; Rennesson, C.; Simon, J.; Pugin, D.; Gasche, Y.
Abstract : Introduction: Faced with increasing shortage of organs in Switzerland, the Federal Office of Public Health(FOPH) published an action plan focused on increasing the number of organs available for transplantation [1] . The aim is to increase the organ donation rate in Switzerland to achieve 20 donors per million population(pmp). Figures published for 2016 show 13.3 donors pmp with a refusal rate of 57% in 2016 [2] . The first 3 points of the action plan concern the hospitals and their staff; specific training and creation of quality systems in Swiss hospitals, which must ensure that there is at least one person who has sufficient time and professional knowledge to deal with organ donation. Historically in Switzerland this role was covered by the intensive care team along with procurement-transplant coordinators. The 4th point concerning information to the general public and creation of campaigns are under the responsibility of the FOPH, in collaboration with Swisstransplant. Methods: Mandatory training for local donor coordinators is provided by Swisstransplant and a certificate of "Swiss expert for organ donation "can be achieved. The Geneva University Hospitals decided to create a donation team, managed by a medical doctor and an experienced coordinator and since January 2017, 7 Specialised Nurses for Organ Donation(SNOD) are involved in the donation process. In March of 2017 a survey was sent to the intensive care team to determine the initial impact of SNODs. Results: 72 replies were analysed: 82% of participants thought SNODs were valuable for teamwork, 75% estimated they were helpful for understanding the donation process and 62% declared an alleviation of their workload. 82% of caregivers believed that SNODs provided additional listening time for relatives and 71% considered that they offer valuable assistance to grieving relatives. Finally, 62% thought that the involvement of SNODs can encourage the acceptance of donation by the relatives. Conclusion: SNODs guarantee the identification of all donors; and they are now involved in the requesting process to help relatives to make the right decision for the deceased, based on what the patient himself would have wanted. The consent rate obtained when they intervene is already very promising: 2 donations after cardiac death(DCD) and 4 donations after brain death with acceptance respectively 80% and 100%. Mean consent rate in our hospital over the past 5 years was 65% (min. 57% max. 81 %). The creation of this new profile of SNODs, dedicated to organ and tissue donation, will improve the care of donors and their relatives, as well as providing support for other caregivers. The SNODs contribute to the development and management of existing programs such as; procurement of corneas and DCD. The measures implemented by the Geneva University Hospitals reflect our institutions' desire to take action on the issue of organ and tissue shortage. References: 1. Federal Office of Public Health, Action Plan: More organs for transplantation.https://www.bag.admin.ch/bag/fr/home/themen/strategien-politik/nationale-gesundheitsstrategien/aktionsplan-transplantationsmedizin.html . 2. Swisstransplant, Swiss National Foundation for Organ Donation and Transplantation: Statisticshttps://www.swisstransplant.org/en/information-material/statistics/ .